A visit to the Sesame Street Hospital : featuring Jim Henson's Sesame Street Muppets - Hautzig, Deborah; Mathieu, Joe, 1949- (New York : Random House/Children's Television Workshop, 1985)
Grover visits the hospital to find out what to expect when he goes to have his tonsils out.
Keywords: Children's stories, American; Hospitals -- Fiction; Medical care -- Fiction; Tonsillectomy -- Fiction; Puppets -- Fiction